Perioperative analgesic modality and effectiveness in paediatric patients who have undergone common major urology surgery - a two-year retrospective study - YT, Tan; CN, Yeoh; M, Azlina; AS, Ahmad; AH, Nurhafiizhoh; MN, Nadia (Penerbit Universiti Kebangsaan Malaysia, 2023)
Perioperative paediatric major urology surgery pain management remains challenging. These surgeries require general anaesthesia (GA) combined with either regional analgesia technique or systemic morphine infusion for optimal pain relief. We aimed to compare and evaluate the effectiveness of both analgesic techniques. This single centre retrospective descriptive study involved 88 patients, aged 3 months to 12 years old with American Society of Anaesthesiologists (ASA) I or II status, who underwent major urology surgery under GA. Group A patients received perioperative systemic morphine while Group B received regional anaesthesia blocks (continuous caudal epidural infusion, single-shot caudal blocks or single-shot erector spinae blocks). We measured requirements of perioperative rescue intravenous (IV) fentanyl, pain scores using Face, Leg, Activity, Cry, Consolability (FLACC) scale, perioperative non-opioid IV analgesia usage and associated complications. Intraoperative rescue fentanyl in both groups was comparable. Intraoperative non-opioid analgesia and postoperative rescue fentanyl requirement were significantly higher in Group A compared to Group B (p<0.001). Median FLACC scores in Group A were higher than Group B (p<0.001) for first 12 hours post-surgery. Commonest complications in Group A was vomiting (38.6%) and peri-catheter leak in Group B (6.81%). Regional anaesthesia technique is superior to systemic morphine in providing analgesia in the first 12 hours post paediatric major urology surgery and is devoid of opioid side effects.